2022
DOI: 10.3390/jintelligence10040089
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Based Development of Reading Skills to Reduce Dropout in Uncertain Times

Abstract: An adequate level of reading comprehension is a prerequisite for successful learning. Numerous studies have shown that without a solid foundation, there can be severe difficulties in later learning and that failure in the first years of schooling can determine attitudes to learning. In the present study, we present the effect size of an online game-based training program implemented on eDia. The primary goals of the development program are to develop fluency in reading and reading comprehension in Grades 3–4. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 74 publications
0
0
0
Order By: Relevance
“…Several studies have indicated that technology may help promote core reading and numeracy. For example, Szili et al (2022)…”
Section: Use Of Technologymentioning
confidence: 99%
“…Several studies have indicated that technology may help promote core reading and numeracy. For example, Szili et al (2022)…”
Section: Use Of Technologymentioning
confidence: 99%
“…Game dapat menjadi media hiburan sekaligus media pengembangan kemampuan serius (Sabirli & Çoklar, 2020). Serious game atau game serius memiliki banyak sekali kegunaan, mulai dari melatih kemampuan membaca anak (Szili et al, 2022), latihan gerak dewasa (Brauner & Ziefle, 2020), latihan penanggulangan bencana (Gampell et al, 2020), desain interior fasilitas umum (Yang et al, 2021), hingga pendidikan praktek antimikroba (del Cura-González et al, 2022). Game serius dalam berbagai bentuk memberikan hasil positif pada pendidikan (Khan et al, 2021).…”
Section: Original Researchunclassified